Cisplatin Binding to Biological Ligands Revealed at the Encounter Complex Level by IR Action Spectroscopy. Issue 11 (8th January 2016) - Corinti, Davide; Coletti, Cecilia; Re, Nazzareno; Chiavarino, Barbara; Crestoni, Maria Elisa; Fornarini, Simonetta
Abstract: Cisplatin [ cis ‐diamminedichloroplatinum(II)] was the first platinum‐based antineoplastic agent and is still a cornerstone for the treatment of various solid tumors. Reactive events responsible for cisplatin activity are unveiled here at the molecular level. Simple ligands (L) representing ubiquitous functional groups in the biological environment likely to be encountered by administered cisplatin have been allowed to react with cis ‐[PtCl(NH3 )2 (H2 O)] +, the primary intermediate from cisplatin hydrolysis. The substitution reactions have been examined by a combined experimental and computational approach and the structural features of the substitution product, cis ‐[PtCl(NH3 )2 (L)] +, have been probed by IR multiple‐photon dissociation (IRMPD) spectroscopy. Furthermore, IRMPD spectroscopy has been exploited to elucidate the structure of [PtCl(NH3 )2 (L)(H2 O)] + clusters, also obtained by electrospray ionization (ESI) from the aqueous solution and representing the major focus of this investigation. These ions conform to the encounter complex of cis ‐[PtCl(NH3 )2 (H2 O)] + with the incoming ligand and represent the first direct evidence of a prototypical Eigen–Wilkins encounter complex in solution, lying on the reaction coordinate for ligand substitution and extracted by ESI for mass spectrometric analysis. Activated [PtCl(NH3 )2 (L)(H2 O)] + ions dissociate by the loss of either H2 O or L, the former process implying a ligand substitution event. IRMPD spectroscopy has thus revealed both structural details and reaction dynamics at the level of the isolated encounter complex. Abstract : Cisplatin activation and interactions : An Eigen–Wilkins encounter complex in the reactant pre‐association mechanism for ligand substitution in solution has been directly identified by electrospray ionization‐mass spectrometry. Key intermediates and reactive events accounting for cisplatin activity have been elucidated in a controlled environment, the gas phase, with unprecedented detail (see figure).